Software industry in the developing countries : the possibilities. - Fialkowski, Konrad (1990)
Discusses the advantages for developing countries of software production, namely (1) that with properly qualified manpower they could produce software at a fraction of its cost in developed countries; and (2) the low investment level needed gives it a substantial advantage. Observes that the one, but substantial, obstacle is the market.